2011
DOI: 10.1111/j.1365-2559.2011.03818.x
|View full text |Cite
|
Sign up to set email alerts
|

HtrA1, a potential predictor of response to cisplatin-based combination chemotherapy in gastric cancer

Abstract: Identification of HtrA1 in gastric cancer prior to chemotherapy indicates that levels of HtrA1 could be used to predict response to platinum-based combination therapies. Further assessment of HtrA1 expression is highly warranted in large, prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 39 publications
3
22
1
Order By: Relevance
“…The mechanism of the enhancement by HtrA1 is very likely to have something to do with its targeting effect on XIAP. HtrA1 is expected to be used for targeting therapy [6,26].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of the enhancement by HtrA1 is very likely to have something to do with its targeting effect on XIAP. HtrA1 is expected to be used for targeting therapy [6,26].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al also reported that HtrA1 could function in chemotherapeutic responsiveness by mediating DNA damage response pathways [8]. Accordingly in ovarian and gastric cancers, low HtrA1 expressions demonstrated a strong association with poor response to cytotoxic chemotherapy [19,20]. Meningiomas are the most common primary brain tumors which arise from arachnoidal cap cells of the meninges.…”
Section: Introductionmentioning
confidence: 95%
“…MAP1B (Microtubule-Associated Protein 1B) has been previously shown to be hypermethylated in CIMP-high tumors without MSI, which mainly correspond to the group of tumors analyzed in our study [36]. HTRA1 is a member of the HTRA (High-Temperature Requirement Factor A) family of serine proteases and plays a protective role in various malignancies due to its tumor suppressive properties [37], [38], [39]. HTRA1 has shown to be silenced through promoter hypermethylation [38], and proposed as a potential novel biomarker for diagnosis and prediction in several cancers.…”
Section: Discussionmentioning
confidence: 58%
“…HTRA1 is a member of the HTRA (High-Temperature Requirement Factor A) family of serine proteases and plays a protective role in various malignancies due to its tumor suppressive properties [37], [38], [39]. HTRA1 has shown to be silenced through promoter hypermethylation [38], and proposed as a potential novel biomarker for diagnosis and prediction in several cancers. ALOX15 (15-lipoxygenase or 15-LOX) is an inducible and highly regulated enzyme in normal human cells that plays a key role in the production of lipid signaling mediators.…”
Section: Discussionmentioning
confidence: 99%